Nature of Communication In The Perspective of Surah Al-Hujarat Verse 11-13 - Dewi Mukarromah; Anita Puji Astutik (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article looks at the morals of communication through the lens of Surah Al-Hujarat Verse 11-13. Sheikh Wahbah Zuhaili's study of Munir's Tafsir. This study aims to educate the public about the value of honest communication. Honest communication is the foundation of life and religion for everyone. Morals instruct us to constantly have excellent character and behavior in our interactions with God and others. The method is qualitative, and it entails data mining or library article. The term "library article" refers to activities involving library data gathering methods, reading and recording article materials, and processing them. The tahlili method was used to translate Surah Al-Hujurat verses 11-13. The study's findings reveal that Allah SWT's admonition and mandate to all humankind is to avoid ridiculing and insulting others first. Second, avoid being prejudiced against people and gossiping about them. Third, by focusing on mutual respect and understanding, people of various ethnicities, customs, languages, cultures, groups, social statuses, and even religions can learn to know one another.